Media Concentration in the Baltic States (2000–2014) - Jastramskis, Deimantas; Rožukalne, Anda; Jõesaar, Andres (Information & Media, 2017)
This article examines media concentration in the Baltic States between 2000 and 2014. The study employs the Herfindahl-Hirschman Index to assess the volatility and the level of horizontal concentration in the media markets of radio, television, daily newspapers and internet of Lithuania, Latvia and Estonia. The analysis reveals that most of the Baltic States’ media markets are highly concentrated and tend towards the creation of oligopolistic competition. Only two markets (the Estonian television and Lithuanian internet market) could be defined as moderately concentrated at the end of the research period.
Keywords: Media concentration; media market; time share; Herfindahl-Hirschman Index; Baltic States